Efektivitas Terapi Aktivitas Kelompok Stimulasi Kognitif terhadap Fungsi Kognitif pada Lansia dengan Mild Cognitive Impairment di Panti Werdha - Fery Agusman MM; Sonhaji; Moch Jamaluddin (Journal of Biomedical Sciences and Health, 2025)
Mild Cognitive Impairment (MCI) merupakan kondisi penurunan fungsi kognitif yang memerlukan intervensi dini untuk mencegah progresivitas menuju demensia. Penelitian ini bertujuan menganalisis efektivitas Terapi Aktivitas Kelompok (TAK) Stimulasi Kognitif dalam meningkatkan fungsi kognitif lansia dengan MCI di Panti Werdha. Menggunakan desain quasi-experimental pre-post test with control group, penelitian melibatkan 60 lansia (30 intervensi, 30 kontrol) yang dipilih melalui purposive sampling. Kelompok intervensi menerima TAK Stimulasi Kognitif dua kali seminggu selama 8 minggu, sementara kelompok kontrol menerima aktivitas rutin panti. Pengukuran fungsi kognitif menggunakan Montreal Cognitive Assessment (MoCA). Hasil menunjukkan peningkatan signifikan skor MoCA pada kelompok intervensi (p<0.001) dibanding kontrol, dengan perbedaan mean 3.8 poin. TAK Stimulasi Kognitif terbukti efektif meningkatkan fungsi kognitif lansia dengan MCI dan potensial diimplementasikan dalam program rutin panti werdha. Keywords: stimulasi kognitif, terapi aktivitas kelompok, mild cognitive impairment, lansia, panti werdha   ABSTRACT Mild Cognitive Impairment (MCI) is a condition of cognitive decline requiring early intervention to prevent progression to dementia. This study aimed to analyze the effectiveness of Group Cognitive Stimulation Therapy (GCST) in improving cognitive function among elderly with MCI in nursing homes. Using a quasi-experimental pre-post test with control group design, the study involved 60 elderly participants (30 intervention, 30 control) selected through purposive sampling. The intervention group received GCST twice weekly for 8 weeks, while the control group participated in routine nursing home activities. Cognitive function was measured using the Montreal Cognitive Assessment (MoCA). Results showed a significant improvement in MoCA scores in the intervention group (p<0.001) compared to the control group, with a mean difference of 3.8 points. GCST proved effective in improving cognitive function among elderly with MCI and shows potential for implementation in routine nursing home programs. Keywords: cognitive stimulation, group activity therapy, mild cognitive impairment, elderly, nursing home